IMPLIKASI HUKUM HAMBATAN YURIDIS PENDAFTARAN TANAH SISTEMATIS LENGKAP TERHADAP KEPASTIAN HUKUM DI KABUPATEN BULELENG - Gede Anggha Indrawan; Ni Putu Ega Parwati; I Made Ambara Jaya (Jurnal Ilmu Hukum Sui Generis, 2026)
Difficulties concerning land persist, impeding the achievement of legal assurance and effective community administration. The government endeavors to address this via the PTSL (Complete Systematic Land Registration), aiming to furnish land certificates that serve as evidence of land ownership for citizens and offer robust legal safeguards. This research adopted a normative legal methodology, characterized by its descriptive approach. The investigative framework incorporated the statute, conceptual, and case approaches. Among the identified legal impediments to the execution of the 2026 PTSL in Buleleng Regency is the issue of incomplete legal documentation, such as land certificates. Community land registration is hindered by legal challenges, impeding their ability to secure official land certificates. Effective program execution necessitates an equilibrium between legal assurance and tangible advantages, facilitated by a verification process that adheres to established legal frameworks. This approach will more effectively achieve the program's objective of providing legal protection and certainty to the community